News 2.0. - Stanik, John (New York ACM, 2006)
Taking a second look at the news so you don't have to
Keywords: General literature; General; Computing Milieux; Computers and society; Electronic commerce; Security; Management of computing and information systems; Security and protection; Miscellaneous